Diversity of Anurans in Rice Fields under Organic and Conventional Management in Santa Fe Province, Argentina - Attademo, Andres Maximiliano (2018)
Therefore, research on organic rice is fundamental and it would allow us to design heterogeneous agroecosystems considering the functional and structural diversity of rice crops. Here, we compare diversity and composition (richness, abundance) of anurans during a rice crop cycle between two (organic and conventional) management systems in Santa Fe province, Argentina.